Graphene / polymer composite anticorrosive coating and preparation method thereof
The graphene/polymer composite anti-corrosion coating uses polypyrrole nanoparticles-nanowires to co-coat graphene powder with hydroxyl acrylic resin to form a multi-scale structure, which solves the problem of insufficient physical barrier and electrochemical protection of traditional coatings under harsh working conditions, and achieves high adhesion and long-lasting anti-corrosion effect.
Patent Information
- Application Number
- CN202511828188.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-05
- Publication Date
- 2026-01-16
AI Technical Summary
Traditional anti-corrosion coatings have limited physical barrier performance, insufficient interfacial adhesion, and inadequate electrochemical protection under harsh working conditions. They cannot dynamically respond to changes in the corrosive environment, resulting in easy penetration and peeling of the coating, and a lack of long-term anti-corrosion capability.
By preparing a graphene/polymer composite anti-corrosion coating, a multi-scale structure is formed by co-coating graphene composite powder with polypyrrole nanoparticles-nanowires and mixing it with hydroxyl acrylic resin. This constructs a synergistic system of physical barrier and electrochemical protection, thereby improving the coating's adhesion and environmental durability.
Excellent adhesion and long-term corrosion resistance of graphene/polymer composite coating are achieved. A three-dimensional conductive network is formed by polypyrrole nanowires to uniformly disperse corrosion current. Polypyrrole nanoparticles fill the gaps between graphene sheets, enhance the resistance to medium penetration, dynamically repair local damage, form a multi-level response mechanism, and improve the corrosion resistance of the coating.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of anti-corrosion coating technology, specifically to a graphene / polymer composite anti-corrosion coating and its preparation method. Background Technology
[0002] Corrosion of metallic materials is a common problem in industrial environments, especially in harsh conditions such as marine and chemical plants. Traditional anti-corrosion coatings (such as epoxy resin and polyurethane) often suffer from problems such as penetration and peeling due to limited physical barrier performance or lack of active protection mechanisms, making it difficult to meet the requirements for long-term corrosion protection. In recent years, graphene has been widely used in the field of anti-corrosion coatings due to its excellent chemical stability, high specific surface area, and sheet barrier properties.
[0003] However, single graphene-reinforced coatings still suffer from insufficient interfacial bonding: the graphene sheets have poor compatibility with the polymer matrix and are prone to agglomeration, leading to stress concentration within the coating and reduced adhesion; the anti-corrosion mechanism is singular: relying solely on the physical barrier effect of graphene ("maze effect"), it cannot dynamically respond to changes in the corrosive environment, and once the coating is partially damaged, the corrosive medium will spread rapidly; electrochemical protection is lacking: traditional coatings lack a conductive network and cannot uniformly distribute the corrosion current, and local galvanic corrosion can easily cause the coating to blister and peel off.
[0004] To address these issues, researchers have attempted to incorporate conductive polymers (such as polyaniline and polypyrrole) into graphene composites. However, in existing technologies, conductive polymers are often simply blended with graphene in a single morphology (such as particles or fibers), which results in insufficient morphology control and low electrochemical protection efficiency.
[0005] Therefore, there is an urgent need to develop a new composite anti-corrosion system that can achieve synergistic effects of physical barrier and electrochemical protection by precisely controlling the multi-scale structure of graphene and conductive polymer, while improving coating adhesion and environmental durability. Summary of the Invention
[0006] In view of this, the purpose of this invention is to propose a graphene / polymer composite coating with excellent adhesion and long-lasting anti-corrosion performance, so as to solve the problems of traditional anti-corrosion coatings having a single physical barrier and insufficient electrochemical protection.
[0007] To achieve the above objectives, the present invention provides a graphene / polymer composite anti-corrosion coating, wherein the composite anti-corrosion coating is obtained by applying a graphene / polymer composite anti-corrosion coating to the surface of a substrate and then curing it. The graphene / polymer composite anti-corrosion coating is prepared from the following raw materials in parts by weight: 0.12-0.24 parts of polypyrrole nanoparticles-nanowires co-coated graphene composite powder, 3-6 parts of butyl acetate, 20-40 parts of hydroxyl acrylic resin, 0.2-0.4 parts of defoamer, 0.2-0.4 parts of leveling agent, and 6.4-12.8 parts of curing agent; Preferably, the substrate is Q235 low-carbon steel.
[0008] Preferably, the hydroxyl acrylic resin has a viscosity of 1000-2000 cps / 30℃ and an acid value of 6-9 mg KOH / g.
[0009] Preferably, the defoamer is one of MOK6020, BYK-A530, and BYK-065.
[0010] Preferably, the leveling agent is one of BYK300, MOK-2038, and BYK-333.
[0011] Preferably, the curing agent is curing agent N75, with an NCO content of 16.5% ± 0.3% and a viscosity (23℃) of 250 ± 75 MPa·s.
[0012] Furthermore, the preparation steps of the polypyrrole nanoparticle-nanowire co-coated graphene composite powder are as follows: Graphene and deionized water were stirred evenly to obtain solution A; pyrrole and ethanol solution were mixed and sonicated to obtain solution B; hexadecyltrimethylammonium bromide was dissolved in deionized water and stirred evenly, pyrrole was added, and the mixture was stirred. The solution was cooled to 4°C in an ice-water bath to obtain solution C; anhydrous ferric chloride and deionized water were mixed and sonicated to obtain solution D; solutions A, B, and C were mixed and stirred at 4-5°C, and solution D was added dropwise. After the addition was complete, the mixture was stirred for 20-24 hours. After the reaction was completed, the product was washed several times with deionized water until the pH was neutral, and then dried at 60°C to obtain polypyrrole nanoparticle-nanowire co-coated graphene composite powder. Preferably, the ratio of graphene to deionized water in solution A is 0.5-1g:25-50mL.
[0013] Preferably, the graphene has a particle size of 50-100 μm.
[0014] Preferably, the ratio of pyrrole to ethanol solution in solution B is 0.5-1.5g:30-40mL.
[0015] Preferably, the ratio of hexadecyltrimethylammonium bromide, deionized water and pyrrole in solution C is 1.05-1.10g:30-35mL:0.8-1.0g.
[0016] Preferably, the ratio of anhydrous ferric chloride to deionized water in solution D is 1.0-3.0 g: 20 mL.
[0017] Furthermore, the present invention also provides a method for preparing a graphene / polymer composite anti-corrosion coating, comprising the following steps: (1) Polypyrrole nanoparticles-nanowires co-coated graphene composite powder and butyl acetate were poured into hydroxy acrylic resin and mixed evenly. The mixture was then transferred to a planetary ball mill and ground for 4 hours. Subsequently, defoamer, leveling agent and curing agent were added and stirred for 5-10 minutes to obtain graphene / polymer composite anti-corrosion coating. (2) Grind, clean and dry the surface of Q235 low carbon steel, apply the obtained coating to the surface of the substrate, and then cure at room temperature for 40-48h to obtain graphene / polymer composite anti-corrosion coating. Preferably, the grinding speed in step (1) is 700-800 rpm.
[0018] Preferably, the polishing in step (2) is performed by sequentially polishing with SiC sandpaper of 80#, 150# and 400#.
[0019] The beneficial effects of this invention are: The graphene sheets of this invention form a physical barrier layer through close stacking, which significantly extends the diffusion path of the corrosive medium; the polypyrrole nanowires intertwine in the coating to form a three-dimensional conductive network, uniformly dispersing the corrosion current and suppressing local electrochemical corrosion; the polypyrrole nanoparticles fill the gaps between the graphene sheets, further reducing coating defects and enhancing the resistance to medium penetration.
[0020] This invention utilizes the redox properties of polypyrrole to induce the formation of a dense passivation film on the surface of a metal substrate. Even if the coating is locally damaged, the exposed area can still be rapidly repaired through electrochemical action. Furthermore, the synergistic distribution of nanowires and nanoparticles forms a multi-level response mechanism, with nanowires providing long-range conductive pathways and nanoparticles enhancing local passivation efficiency.
[0021] This invention enables polypyrrole and graphene to form a strong interfacial bond through π-π conjugation. The fibrous structure of nanowires is interwoven in the resin matrix, which improves the stress transfer efficiency within the coating. Furthermore, the core-shell structure of the composite filler (graphene as the core and polypyrrole as the shell) avoids filler agglomeration, ensuring its uniform dispersion in the resin and reducing stress concentration. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0023] The sources or properties of the raw materials used in the embodiments and comparative examples of this invention are as follows: Hydroxyacrylate resin: Tongde ACR6780, viscosity 1000-2000cps / 30℃, acid value 6-9mgKOH / g; curing agent: Covestro curing agent N75, NCO content 16.5%±0.3%, viscosity (23℃) 250±75Mpa·s; defoamer: MOK6020; leveling agent: BYK300; graphene: 50-100μm.
[0024] Example 1: A graphene / polymer composite anti-corrosion coating, the specific preparation steps are as follows: (1) Mix 0.5g graphene and 25mL deionized water evenly and sonicate for 30min to obtain solution A; mix 0.5g pyrrole with 30mL ethanol solution and sonicate for 30min to obtain solution B; dissolve 1.05g hexadecyltrimethylammonium bromide in 30mL deionized water, stir evenly, add 0.8g pyrrole, stir for 10min, and cool the mixed solution to 4℃ in an ice water bath to obtain solution C; mix 1.0g anhydrous ferric chloride with 20mL deionized water and sonicate for 30min to obtain solution D; mix solutions A, B and C at 4-5℃, add solution D dropwise, stir for 20h after the addition is complete, wash the product obtained after the reaction is complete with deionized water several times until the pH is neutral, and dry at 60℃ to obtain polypyrrole nanoparticle-nanowire co-coated graphene composite powder; (2) 0.12g of polypyrrole nanoparticles-nanowires co-coated graphene composite powder and 3g of butyl acetate were poured into 20g of hydroxyl acrylic resin and mixed evenly. The mixture was then transferred to a planetary ball mill and ground at 700rpm for 4h. Subsequently, 0.2g of defoamer, 0.2g of leveling agent and 6.4g of curing agent N75 were added and stirred for 5min to obtain graphene / polymer composite anti-corrosion coating. (3) Q235 low carbon steel is selected as the substrate. Before coating, the surface of the low carbon steel is polished with 80#, 150# and 400# SiC sandpaper in sequence, then rinsed with deionized water and anhydrous ethanol, and dried in a vacuum drying oven at 50°C. The obtained coating is applied to the substrate surface with a 200μm four-sided coating tool, and then cured at room temperature for 40h to obtain a graphene / polymer composite anti-corrosion coating.
[0025] Example 2: A graphene / polymer composite anti-corrosion coating, the specific preparation steps are as follows: (1) 0.75g graphene and 40mL deionized water were stirred evenly and sonicated for 30min to obtain solution A; 1.0g pyrrole was mixed with 35mL ethanol solution and sonicated for 30min to obtain solution B; 1.08g hexadecyltrimethylammonium bromide was dissolved in 33mL deionized water, stirred evenly, 0.9g pyrrole was added, stirred for 10min, and the mixed solution was cooled to 4℃ in an ice water bath to obtain solution C; 2.0g anhydrous ferric chloride was mixed with 20mL deionized water and sonicated for 30min to obtain solution D; at 4-5℃, solutions A, B and C were mixed and stirred, and solution D was added dropwise. After the addition was completed, the mixture was stirred for 22h. After the reaction was completed, the product was washed several times with deionized water until the pH was neutral, and dried at 60℃ to obtain polypyrrole nanoparticle-nanowire co-coated graphene composite powder. (2) 0.18g of polypyrrole nanoparticles-nanowires co-coated graphene composite powder and 4.5g of butyl acetate were poured into 30g of hydroxyl acrylic resin and mixed evenly. The mixture was then transferred to a planetary ball mill and ground at 750rpm for 4h. Subsequently, 0.3g of defoamer, 0.3g of leveling agent and 9.6g of curing agent N75 were added and stirred for 8min to obtain graphene / polymer composite anti-corrosion coating. (3) Q235 low carbon steel is selected as the substrate. Before coating, the surface of the low carbon steel is polished with 80#, 150# and 400# SiC sandpaper in sequence, then rinsed with deionized water and anhydrous ethanol, and dried in a vacuum drying oven at 50°C. The obtained coating is applied to the substrate surface with a 200μm four-sided coating tool, and then cured at room temperature for 44h to obtain a graphene / polymer composite anti-corrosion coating.
[0026] Example 3: A graphene / polymer composite anti-corrosion coating, the specific preparation steps are as follows: (1) Stir 1g of graphene and 50mL of deionized water evenly and sonicate for 30min to obtain solution A; mix 1.5g of pyrrole with 40mL of ethanol solution and sonicate for 30min to obtain solution B; dissolve 1.10g of hexadecyltrimethylammonium bromide in 35mL of deionized water, stir evenly, add 1.0g of pyrrole, stir for 10min, and cool the mixed solution to 4℃ in an ice water bath to obtain solution C; mix 3.0g of anhydrous ferric chloride with 20mL of deionized water and sonicate for 30min to obtain solution D; mix solutions A, B and C at 4-5℃, add solution D dropwise, stir for 24h after the addition is complete, wash the product obtained after the reaction is complete with deionized water several times until the pH is neutral, and dry at 60℃ to obtain polypyrrole nanoparticle-nanowire co-coated graphene composite powder; (2) 0.24g of polypyrrole nanoparticles-nanowires co-coated graphene composite powder and 6g of butyl acetate were poured into 40g of hydroxyl acrylic resin and mixed evenly. The mixture was then transferred to a planetary ball mill and ground at 800rpm for 4h. Subsequently, 0.4g of defoamer, 0.4g of leveling agent and 12.8g of curing agent N75 were added and stirred for 10min to obtain graphene / polymer composite anti-corrosion coating. (3) Q235 low carbon steel was selected as the substrate. Before coating, the surface of the low carbon steel was polished with 80#, 150# and 400# SiC sandpaper in sequence, then rinsed with deionized water and anhydrous ethanol, and dried in a vacuum drying oven at 50°C. The obtained coating was applied to the substrate surface with a 200μm four-sided coating tool, and then cured at room temperature for 48h to obtain a graphene / polymer composite anti-corrosion coating.
[0027] Comparative Example 1: The difference from Example 2 is that in step (1), solution C is replaced with an equal amount of solution B, and the rest of the steps are the same as in Example 2.
[0028] Comparative Example 2: The difference from Example 2 is that in step (1), solution B is replaced with an equal amount of solution C, and the rest of the steps are the same as in Example 2.
[0029] Comparative Example 3: The difference from Example 2 is that in step (2), the polypyrrole nanoparticle-nanowire co-coated graphene composite powder is replaced with graphene powder, and the other steps are the same as in Example 2.
[0030] Performance testing Adhesion: The adhesion of the coating was tested using the pull-out method according to ISO 4624-2002, and the test was conducted using a ZR-FZL-M digital display pull-out adhesion tester. Neutral salt spray test: Electrochemical measurements were performed using an electrochemical workstation (Reference 620, Garmy) with a three-electrode system. A carbon rod was used as the counter electrode, a saturated calomel electrode as the reference electrode, and the sample as the working electrode. 3.5% NaCl solution was used as the electrolyte. The test frequency range was 10 Hz. -2 -10 5 Hz, AC signal amplitude of 10mV, according to ISO 9227-2017, neutral salt spray (NSS) test was conducted using a salt spray test chamber (ASR-90A); observe and record the time when the coating blistered; Self-healing performance: The self-healing ability of the coating was evaluated by scratch-healing cycle test. Standard scratches (50 mm in length, 100 μm in width, and depth to the substrate) were made on the coating surface using a diamond scratcher. The test specimens were then placed in an environment of 60°C and 80% relative humidity for 24 h. The test results are shown in Table 1.
[0031]
[0032] Data Analysis: As can be seen from the data in Examples 1-3 of Table 1, the graphene / polymer composite anti-corrosion coating prepared in this invention exhibits excellent comprehensive performance. The three-dimensional network structure formed through in-situ polymerization not only effectively fills the pores and defects inside the coating but also constructs a multi-scale anti-corrosion barrier system. First, graphene nanosheets, with their ultra-high specific surface area and layer stacking characteristics, significantly extend the diffusion path of corrosive media through the "maze effect." Second, the introduction of polypyrrole endows the coating with active protection capabilities—its conductive properties promote the formation of a dense passivation film on the metal substrate surface. Simultaneously, the nanowire structure forms a continuous conductive pathway in the coating, guiding the uniform distribution of corrosion current and inhibiting the occurrence of localized galvanic corrosion. Furthermore, the synergistic distribution of polypyrrole nanoparticles and nanowires enhances the interfacial bonding force with the graphene sheets and optimizes stress transmission through hierarchical structure. This allows the coating to maintain high adhesion while its internal nanocomposite phase can dynamically respond to changes in the corrosive environment. This coupling effect of the physical-chemical dual protection mechanism enables the coating system to exhibit long-term and stable corrosion protection capabilities.
[0033] The differences in performance data between Example 2 and Comparative Examples 1 and 2 in Table 1 suggest that the synergistic effect of polypyrrole nanowires and nanoparticles has a key impact on improving coating performance. Nanowire structures construct a three-dimensional conductive network in the coating, which can uniformly disperse corrosion current and suppress localized electrochemical corrosion. Nanoparticles, filling the spaces between graphene sheets, form an interlocking structure with the nanowires, enhancing the physical barrier effect and improving interfacial bonding with graphene through π-π conjugation. When solution C is missing (Comparative Example 1), the lack of surfactant morphology regulation results in polypyrrole existing mainly as random particles, making it difficult to form a continuous conductive network. When solution B is missing (Comparative Example 2), insufficient pyrrole monomers reduce the degree of polymerization of polypyrrole, limiting nanowire growth. Both situations weaken the functional modification effect of polypyrrole on graphene, thus affecting the dispersion and interfacial bonding strength of the composite filler in the resin matrix. In particular, the size difference between nanowires and nanoparticles may create a multi-level void structure. This micro-nano-scale structural gradient can effectively hinder the penetration and diffusion of corrosive media. Simultaneously, nanoparticles and nanowires can uniformly disperse corrosion current and suppress localized electrochemical corrosion, thus macroscopically resulting in simultaneous optimization of coating adhesion and salt spray resistance.
[0034] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.
Claims
1. A graphene / polymer composite anticorrosive coating, characterized by, The composite anticorrosive coating is obtained by coating and curing the graphene / polymer composite anticorrosive paint on the surface of the substrate; The graphene / polymer composite anticorrosive paint is prepared from the following raw materials in parts by weight: 0.12-0.24 parts of polypyrrole nanoparticle-nanowire co-coated graphene composite powder, 3-6 parts of butyl acetate, 20-40 parts of hydroxyl acrylic resin, 0.2-0.4 parts of defoaming agent, 0.2-0.4 parts of leveling agent, and 6.4-12.8 parts of curing agent. The preparation steps of the polypyrrole nanoparticle-nanowire co-coated graphene composite powder are as follows: Mix graphene and deionized water to obtain solution A; mix pyrrole and ethanol solution to obtain solution B; dissolve cetyltrimethylammonium bromide in deionized water, add pyrrole, and cool to 4℃ in an ice bath to obtain solution C; mix anhydrous ferric chloride and deionized water to obtain solution D; mix solutions A, B, and C at 4-5℃, add solution D dropwise, and stir for 20-24h to obtain polypyrrole nanoparticle-nanowire co-coated graphene composite powder.
2. The graphene / polymer composite anticorrosive coating according to claim 1, characterized in that, The use amount ratio of graphene to deionized water in solution A is 0.5-1g:25-50mL; the use amount ratio of pyrrole to ethanol solution in solution B is 0.5-1.5g:30-40mL.
3. The graphene / polymer composite anticorrosive coating according to claim 1, wherein The use amount ratio of cetyltrimethylammonium bromide, deionized water, and pyrrole in solution C is 1.05-1.10g:30-35mL:0.8-1.0g; the use amount ratio of anhydrous ferric chloride to deionized water in solution D is 1.0-3.0g:20mL.
4. The graphene / polymer composite anticorrosive coating according to claim 1, wherein The substrate is Q235 low-carbon steel.
5. The graphene / polymer composite anticorrosive coating according to claim 1, wherein The viscosity of the hydroxyl acrylic resin is 1000-2000cps / 30℃, and the acid value is 6-9mgKOH / g.
6. The graphene / polymer composite anticorrosive coating according to claim 1, wherein The defoaming agent is one of MOK6020, BYK-A530, and BYK-065; the leveling agent is one of BYK300, MOK-2038, and BYK-333.
7. The graphene / polymer composite anticorrosive coating according to claim 1, wherein The curing agent is curing agent N75 with an NCO content of 16.5%±0.3% and a viscosity (23℃) of 250±75Mpa·s.
8. The graphene / polymer composite anticorrosive coating according to claim 1, wherein The composite anticorrosive coating is prepared by the following steps: (1) mix and grind polypyrrole nanoparticle-nanowire co-coated graphene composite powder, butyl acetate, and hydroxyl acrylic resin, add defoaming agent, leveling agent, and curing agent, and obtain graphene / polymer composite anticorrosive paint; (2) polish, clean, and dry the surface of the substrate, coat the obtained paint on the surface of the substrate, and then cure at room temperature for 40-48h to obtain a graphene / polymer composite anticorrosive coating.
9. The graphene / polymer composite anticorrosive coating according to claim 8, wherein, The rotation speed of the grinding in step (1) is 700-800rpm.
10. The graphene / polymer composite anticorrosive coating according to claim 8, wherein The polishing in step (2) is polishing with SiC sandpaper of 80#, 150#, and 400# in sequence.